Los entornos de validación en la resolución de problemas matemáticos - Alida Mónica Masachs; Germán Edgardo Camprubí; Mauricio Naudi (Universidad Veracruzana, 2012)
El propósito de este artículo es mostrar dos años de experiencia con la resolución de problemas matemáticos en el aula. El foco de la experiencia estuvo puesto en la creación de entornos de validación con intercambio de informaciones y argumentos. Los problemas seleccionados se agruparon en tres niveles para promover la interacción y el debate colectivo en el aula. Abstract The purpose of this article is to show a two year experience dealing with problem solving in Math. The focus is in the process by which the teacher and students constitute social norms and mathematical practices in the course of their classroom interaction. Different problems were solved so as to promote mathematical signs and symbols (ciphers, letters, variables, graphics, diagrams, visualisations, etc.), and social signs and symbols (in the frame of the classroom culture: hidden hints, remarks, reinforcements, confirmations, reflections, etc.) made by the teacher, and comments and remarks of similar types made by other students.